All My Parents: Professional Transgenerational Trauma in the TA Community. (2nd October 2019) - Gheorghe, Nicoleta; Brunke, Marina; Deaconu, Diana; Gheorghe, Alexandra; Ionas, Lucia
Abstract: In this article, the authors introduce the term transgenerational professional trauma and discuss aspects of its existence and transmission in the transactional analysis community. They first define the terms and describe the theory they use in understanding the transmission of transgenerational professional trauma. They make a historical diagnosis following three generations of professional parents: Sigmund Freud, Eric Berne, and Jacqui Schiff. Based on their lived experience, the authors make a phenomenological diagnosis of the echo that this trauma has left within them as a subsequent generation. A case illustration regarding the Romanian TA community is offered. Following that analysis, the authors notice certain patterns emerging that, in their understanding, contain significant information about "that which was impossible to fully permit and impossible to completely forget" (Gerson, 2016, p. 202). In the end, the authors attempt to find meaning for the transgenerational professional trauma in their community. Their goal is to open a space for discussion, inviting the witnessing function of the community.